Artificial intelligence and internet of things in screening and management of autism spectrum disorder. (November 2021) - Ghosh, Tapotosh; Banna, Md. Hasan Al; Rahman, Md. Sazzadur; Kaiser, M. Shamim; Mahmud, Mufti; Hosen, A. S. M. Sanwar; Cho, Gi Hwan
Highlights: Thoroughly reviewed the efficacy of AI and IoT in screening and managing autism. Discussed the integration of smart city facilities for autistic people. Challenges in autism screening and management have been discussed. Research scopes in this field have been pointed out and described. Abstract: Autism is a disability that obstructs the process of a person's development. Autistic individuals find it extremely difficult to cope with the world's pace, can not communicate properly, and unable to express their feelings appropriately. Artificial Intelligence (AI), Machine Learning (ML), and Internet of Things (IoT) are used in several medical applications, and autistic individuals can be assisted using the proper use of automated systems. In this paper, some of the research works in the field of application of AI, ML, and IoT in autism were reviewed. State-of-the-art articles were collected and around 58 articles were selected which have significant contribution in this field. The selected research works were analyzed, represented, and compared. Finally, incorporation of the autism facilities in smart city environment is described, some research gaps and challenges were pointed out, and recommendations were provided for further research work.